Sarus Crane in Indian Mythology and Culture - Kumar Adesh; Kanaujia Amita (International Journal of Life Sciences, 2017)
The Sarus crane is known for its immense cultural contribution is the tallest flying bird and globally ’Vulnerable’ species as per IUCN Red List of Threatened Species. It is the ‘state bird’ of Uttar Pradesh of India. The cultures of various communities not only in India but from all over the world have mentioned about Sarus such as Nepal, Vietnamese, Chinese and Cambodia. Many myths are associated with Sarus. This bird is also known as the eternal symbol of unconditional love and devotion and good fortune. Sarus has a special position in social folklores and this is reflected in its mention in some Indian folk stories and songs. From the ancient to modern time many painters, artists and workers are concerning the Sarus crane in their paintings, architectures, embroideries, handicrafts. India Post also launched a postal stamp on Sarus crane. Presence of Sarus crane is good sign of rainfall and healthy wetlands ecosystem. Various Government departments, Universities, Scientists and Conservationists are coming together to work for Sarus conservation which includes both ex-situ and in-situ measures. Since we are depleting our wetlands which direct affect the Sarus day by day, World Wetlands Day (2nd February) is being celebrated all over the world to make the future generation sensitive about the dilemma of Sarus.